Phylogenomics revealed migration routes and adaptive radiation timing of Holarctic malaria mosquito species of the Maculipennis Group - Yurchenko, Andrey A.; Naumenko, Anastasia N.; Artemov, Gleb N.; Karagodin, Dmitry A.; Hodge, James M.; Velichevskaya, Alena I.; Kokhanenko, Alina A.; Bondarenko, Semen M.; Abai, Mohammad R.; Kamali, Maryam; Gordeev, Mikhail I.; Moskaev, Anton V.; et al. (BMC Biology, 2023)
Background Phylogenetic analyses of closely related species of mosquitoes are important for better understanding the evolution of traits contributing to transmission of vector-borne diseases. Six out of 41 dominant malaria vectors of the genus Anopheles in the world belong to the Maculipennis Group, which is subdivided into two Nearctic subgroups (Freeborni and Quadrimaculatus) and one Palearctic (Maculipennis) subgroup. Although previous studies considered the Nearctic subgroups as ancestral, details about their relationship with the Palearctic subgroup, and their migration times and routes from North America to Eurasia remain controversial. The Palearctic species An. beklemishevi is currently included in the Nearctic Quadrimaculatus subgroup adding to the uncertainties in mosquito systematics. Results To reconstruct historic relationships in the Maculipennis Group, we conducted a phylogenomic analysis of 11 Palearctic and 2 Nearctic species based on sequences of 1271 orthologous genes. The analysis indicated that the Palearctic species An. beklemishevi clusters together with other Eurasian species and represents a basal lineage among them. Also, An. beklemishevi is related more closely to An. freeborni, which inhabits the Western United States, rather than to An. quadrimaculatus, a species from the Eastern United States. The time-calibrated tree suggests a migration of mosquitoes in the Maculipennis Group from North America to Eurasia about 2025 million years ago through the Bering Land Bridge. A Hybridcheck analysis demonstrated highly significant signatures of introgression events between allopatric species An. labranchiae and An. beklemishevi. The analysis also identified ancestral introgression events between An. sacharovi and its Nearctic relative An. freeborni despite their current geographic isolation. The reconstructed phylogeny suggests that vector competence and the ability to enter complete diapause during winter evolved independently in different lineages of the Maculipennis Group. Conclusions Our ...